MAPLE PROCEDURES FOR ANALYZING THE ACCURACY OF THE APPROXIMATE DEVELOPMENTS OBTAINED USING GORE METHOD - Mădălina Roxana BUNECI (Fiabilitate şi Durabilitate)
The purpose of this paper is provide Maple procedures to quantify how close are the original 3D-object and the 3D-object formed using an approximate development obtained by applying the well-known gore method to a surface of revolution.